PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF DAN KOMPETITIF DALAM MENGEMBANGKAN KREATIVITAS SISWA - Aziz, Rahmat (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2008)
Both cooperative and competitive methods are influence the student creativity. However, base on the research study the cooperative method understood is more effective than competitive method in developing student creativity. Therefore, using both methods (cooperative and competitive) should be tried in learning process in classes. Keyword: Learning, Cooperative, Competitive, Creativity